2006
DOI: 10.1016/j.ica.2005.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Separation of actinides and lanthanides: Synthesis and molecular structure of a new di-μ-phenoxo-bridged dinuclear bis(dioxouranium(VI)) complex

Abstract: The new phenoxo-bridged uranyl [(UO 2 ) 2 L 2 (thf) 2 ] [H 2 L = N(2-oxyphenyl)-3-methoxy salicylaldiminato (C 14 H 11 NO 3 )] compound has been synthesized and characterized. The 3D structure of the free ligand is also reported. The complex crystallizes in the monoclinic space group P2 1 /c with lattice parameters a = 19.5915(15) Å , b = 10.4096(9) Å , c = 17.5216(14) Å and b = 99.9960(7)°with z = 4. The compound consists of a dinuclear unit composed of two dioxouranium(VI) ions, bridged by two phenoxide oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The analysis showed that the compound is a dialkoxo-bridged diuranyl(VI) compound containing two deprotonated Schiff base ligands, [L] (7) Å) as expected due to π-back bonding. All the bond distances are in the usual ranges observed in the related compounds [13,18,19,[29][30][31].…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The analysis showed that the compound is a dialkoxo-bridged diuranyl(VI) compound containing two deprotonated Schiff base ligands, [L] (7) Å) as expected due to π-back bonding. All the bond distances are in the usual ranges observed in the related compounds [13,18,19,[29][30][31].…”
Section: Resultsmentioning
confidence: 63%
“…The metal-ligand bond distances lie in three distinct ranges with the decreasing order U-O(water/imine) (2.491(7)-2.563(7) Å) > U-O(phenoxo) (2.240(6)-2.280(6) Å) > U-O(uranyl) (1.777(6)-1.792(6) Å). All the bond distances are in the usual ranges [13,18,19,[29][30][31]. The transoid angle (178.9(3)° for unit 1 and 177.6(3)° for unit 2) involving the axial uranyl oxygens and the cisoid angles (85.5(3)°-93.5(3)° for unit 1 and 84.5(3)°-93.4(3)° for unit 2) involving the axial oxygens and five donor atoms in the basal plane show slight deviation from ideal values.…”
Section: (4)⋅⋅⋅h(7e)-c(7e) Hydrogen Bond or Due To The O(4)⋅⋅⋅h(13ch)mentioning
confidence: 99%
See 1 more Smart Citation
“…The diprotic Schiff base ligand (E)-2-(2-hydroxy-3-methoxybenzylideneamino)-phenol (H 2 L1, Scheme 1) initially reported in 1971 to capturing UO 2 [66] can be synthesised in almost quantitative yields [67] and has two pockets that can coordinate to metal centres. Previously, this ligand has been involved in the synthesis of homometallic [68][69][70][71] and heterometallic CCs [72][73][74][75].…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…1 Several methods have been described for the separation and determination of uranyl ion, e.g. complexation, 2 organic sorption and adsorption, 3,4 solvent extraction, 5 coprecipitation, 6 interaction with resins, 7,8 molecularly imprinted ion exchange resin, 9 calorimetry 10 and modified supercritical fluid CO 2 .…”
Section: Introductionmentioning
confidence: 99%